DYNAMICS OF INDICATORS OF MARKERS OF BONE METABOLISM IN BONE DEFECT REPLACEMENTFABRIC EQUIVALENTS OF BONE TISSUE ON THE BASIS OF MMSC-AT - A.V. Bambuliak; P.P. Perebujnis; S.V. Tkachuk; A.V. Javorskiy (Ukrainian Medical Stomatological Academy, 2019)
Bone tissue is one of the most commonly transplantable and inferior to blood components only. The "gold standard" is still considered to be an autologous bone transplant, but this method has some drawbacks associated with additional surgery. The alternative is the use of allogeneic bone, but in this case there is a risk of immunological rejection of the donor bone and the possibility of infection of the recipient. A promising area for the replacement of volumetric bone defects is the creation of bioimplants based on synthetic biocompatible materials impregnated with growth factors that stimulate bone remodeling, or the settlement of stem (multipotent) cells. Most often, mesenchymal multipotent stromal cells are used for settlement. The aim of the study: to find out the level of expression of BGP, Col 1, VEGF genes as indicators of bone repair and mineralization by replacement of bone defects with tissue equivalents of bone tissue based on multipotent mesenchymal stromal cells from adipose tissue. Materials and methods.The experiment was conducted on the Wistar line rats, weighing 200-250 grams, which were divided into VI groups. A bone defect model was formed in the parietal section of the skull of rats. The formed defect implanted the harvested material. Reverse transcription PCR (OG-PCR) was used to quantify mRNA expression for the BGP-bone marker gla protein; VEGF is a vascular endothelial growth factor and Sol 1 (type 1 collagen). Total RNA was isolated from bone tissue by a standard phenol-chloroform-guanidinisothiocyanate method using a set of RNA-Extra reagents to isolate RNA from blood, tissues, cell cultures in several steps according to the manufacturer's recommendations. The data obtained were processed using Bio-Rad CFX Manager 3.0.The obtained results are processed statistically. Research results and their discussion.The highest number of copies of the BGP gene, at 90 days of observations, was determined in experimental animals of the II and III experimental groups (6,280 ± 0,70 and 6,380 ± 0,72, respectively), the number of which did not differ in statistical significance from the data in the animals of the control group, р˃0.05. However, in animals of IV, V and VI groups the number of copies of BGP-gene was 1.5, 1.4 and 1.6 times smaller in relation to the data in intact rats, p0.05, and did not differ in statistical significance , p1 - p4˃0.05. After 3 months of studies determined the decrease in the activity of the production of the gene Col 1. It was noted that the value of the parameter studied in all study groups was equal to the data in intact animals of group I, p0,05 and among themselves, p1 - p4 р0,05, and ranged from the lowest values in group VI rats - 5,192 ± 0,74, and maximum values in group II animals - 6,200 ± 0,88. After 90 days of experimental studies, the high activity of VEGF gene production in experimental animals, which was equal to the data in control rats, p0,05 was investigated. The maximum activity of VEGF gene production was determined in animals of groups IV, II and VI and ranged from 1,200 ± 0,21 copies in group VI to 1,260 ± 0,22 copies in group IV. Conclusions.Thus, according to molecular genetic analysis of the number of cDNA copies encoding BGP, Col 1 and VEGF genes, the most positive changes that contributed to bone repair, mineralization, and complete closure of the defect were observed with the replacement of bone defects in IVa VI specimens.